Radiation situation on the territory of the peaceful nuclear explosion «Globus-1» after performing the rehabilitation works - E. V. Khramtsov (Радиационная гигиена)
The article provides data on the radiation situation on the research of the year 2018 territory adjacent to the site of the peaceful nuclear explosion “Globus-1” after carrying out rehabilitation works (2014-2015), made with the purpose of removal accidental contamination. We analyzed the dynamics of radiation situation during the period from 2008 to 2018 year and assessed the effectiveness of rehabilitation works on basic indicators: the values of the dose of technogenic radionuclides content in soil, water and other objects the environment. According to the results of comparing the number of measurements exceeding the dose rate of 50 nSv/h (background value for outside contamination 2014 years) in samples of 2014 and 2018 years found that 80% of exceedances, enshrined in the year 2014, percentage of exceedances in 2018 year amounted to only 3%. Another performance indicator associated with the feature to the rehabilitation of this object. A large number of low level activity in soil was inappropriate to remove the burial and the decision to use the ground as a lower layer of reclamation was justified. Research has shown that in the spectral composition of gamma background rehabilitated territory intensity peaks of caesium-137 is many times greater than background levels. In selected soil samples recorded elevated levels of cesium-137 (up to 32500 Bq/kg on wet weight), and collected on such soil samples of herbs have elevated concentrations of cesium-137 (up to 2000 Bq/kg) and strontium-90 (up to 400 Bq/kg)on the dry weight basis. All elevated levels of activity concentration of cesium-137 were found in local areas, within the path of radioactive contamination, selected in year 2014. After carrying out rehabilitation work there has been a significant decrease in the levels of external radiation man-made radionuclides and on formal grounds completed rehabilitation work provided the requirement of Russian Safety Norms 2.6.1. 2819-10 and radiation dose does not exceed 0.3 mSv/year, however, high dose rate recorded in separate locations on the recultivated territories indicate incomplete and insufficient as completed rehabilitation.